2014
DOI: 10.1109/tdei.2014.6832268
|View full text |Cite
|
Sign up to set email alerts
|

Insulation characteristics of epoxy insulator with internal crack-shaped micro-defects - study on the equivalence of accelerated degradation by frequency acceleration test

Abstract: Generally, insulating spacers of gas insulated switchgear (GIS) have outstanding durability and are not considered prone to insulation failure within a design life of about 30 years, provided the products conform and have passed the partial discharge (PD) test. However, to assume operation over 30 years, degradation characteristics are important in cases where an extremely microscopic defect below the detection level in the PD test is present or produced inside the insulator. Accordingly, to date, the authors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The frequency of the AC voltage was 1.1 kHz to accelerate insulation deterioration. A previous study reported that insulation lifetime is inversely proportional to the frequency of the AC voltage at a frequency of up to 1.5 kHz [4]. In addition, the PD magnitude q a of one in ten samples was continuously acquired until dielectric breakdown using a current transformer (CT) (Pearson, Model 2877, bandwidth: 300 Hz to 200 MHz).…”
Section: Lifetime Test Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of the AC voltage was 1.1 kHz to accelerate insulation deterioration. A previous study reported that insulation lifetime is inversely proportional to the frequency of the AC voltage at a frequency of up to 1.5 kHz [4]. In addition, the PD magnitude q a of one in ten samples was continuously acquired until dielectric breakdown using a current transformer (CT) (Pearson, Model 2877, bandwidth: 300 Hz to 200 MHz).…”
Section: Lifetime Test Setupmentioning
confidence: 99%
“…Many studies have investigated the deterioration of the insulator due to the PDs in the voids. Studies have focused on the voltage-time characteristics (V-t) [3][4][5], time variation of the PD magnitude and pressure in the void [6], and the relationship between insulation deterioration and chemical reactions based on chemical analysis of the void surface deteriorated through PDs [7,8]. However, minimal research has been paid to the relationship between the void size and insulation lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…Various PD properties in the enclosed void have been investigated experimentally [9,10] and by numerical simulations [10,11]. However, for the void defect, the long-term electrical insulation lifetime property is more important to ensure the insulation reliability of the apparatus [12]. This is because a remained void could cause continuous PDs and the resulting gradual degradations of the solid insulation materials even under the operating voltage, while it doesn't lead to the immediate breakdown.…”
Section: Introductionmentioning
confidence: 99%